A Tale of Two Assets: The Effects of Firm Reputation and Celebrity on Earnings Surprises and Investors' Reactions - Pfarrer, Michael D.; Pollock, Timothy G.; Rindova, Violina P. (Academy of Management Journal, 2010)
The effects of intangible assets on organizational outcomes remain poorly understood. We compare the effects of two intangible assets—firm reputation and celebrity—on (1) the likelihood that a firm announces a positive or negative earnings surprise, and (2) investors' reactions to these surprises. We find that firms that have accumulated high levels of reputation ("high-reputation" firms) are less likely, and firms that have achieved celebrity (celebrity firms) more likely to announce positive surprises than firms without these assets. Both high-reputation and celebrity firms experience greater market rewards for positive surprises and smaller market penalties for negative surprises than other firms.